Essays in corporate governance and social capital : Theses and Dissertations Archive (2005)
These essays study the effects of corporate governance and social capital on firm characteristics such as firm performance and firm value. The first essay addresses with the relationships between ownership concentration, financial performance, and economic characteristics of Colombian firms. Using panel data for 144 firms that issue securities in the Colombian economy between the years 1995 and 2003, we study the determinants of ownership and accounting performance. We find a strong inverse U-shaped effect of earnings variation on ownership concentration, and a U-shaped effect of earnings variation on accounting performance. Additionally, accounting performance positively affects ownership concentration, and ownership concentration affects accounting performance, although the tendency of its effect is not clear. After controlling for endogeneity, we find that ownership concentration has a nonmonotonic effect on accounting performance, with an initial negative effect and, as the ownership becomes highly concentrated, a positive effect.